Nekrotizující pankreatitida a nĕkteré její kómplikace chirurgicky resené - Michek, J; Necas, F; Viktora, P; Wechsler, J; Jagos, F (Rozhledy v chirurgii, 1990)
The authors have summed up their 10-years experiences (1978-1987) with the therapy of acute necrotizing pancreatitis and of some serious surgical complications. While in 252 patients operated early for biliary pancreatitis mortality rate did not exceed 8.7% in 65 patients operated for necrotizing abscessing pancreatitis and its complication it was as many as 63%. The stress has been laid both on early operations of biliary tract diseases and the prevention of developing severe forms of pancreatitis. Even in the cases of advanced necrotizing pancreatitis, priority has been given to radical necrectomy as early as in the second week of the disease duration supplemented with lavage and profuse drainage. The maintenance of therapeutical laparostomy is suitable.
Keywords: Postoperative Complications; pankreatitida; Necrosis; lidé; pooperační komplikace; nekróza; Humans; Pancreatitis